SLC22A1, SLC22A2, SLC22A3 and 11ßHSD1 gene polymorphisms among Malaysian Indians with type 2 diabetes mellitus - Abood, Al Ashoor Sabah Ghasan (2019)
According to the National Health and Morbidity Surveys (NHMS) in Malaysia conducted the most comprehensive and nationally representative available health data of adults have shown that there has been an increasing trend in the reported prevalence of DM for almost the past two decades. Malaysia is a multi-ethnic country whose population of 28.3 million includes three major ancestral groups: Malay (~ 63%), Chinese (~ 25%) and Indian (~ 7%). The prevalence of Type 2 diabetes in the Malaysian population appears to differ among the three major ethnic groups, with Indians having the highest prevalence (25–28%), followed by those of Malay (17– 19%), and the lowest apparent prevalence being among those of Chinese (9–14%). Several studies in various populations have been done to determine the candidate genes with T2DM, but there have been no similar studies that had been found with T2DM among Indian population in Malaysia. The main objective of the study was to determine the candidate genes polymorphisms related to T2DM among Indian population in Malaysia. This study conducted as a cross-sectional study between subjects with T2DM and subjects without T2DM to determine the association of these polymorphisms with T2DM. Based on the inclusion and exclusion criteria, blood samples were collected from 132 samples (Indians) with T2DM and 133 samples as controls. Genomic DNA was extracted from peripheral blood using commercially available kits and genotyping analysis for SLC22A1, SLC22A2, SLC22A3 and 11ßHSD1gene polymorphisms are analyzed using the PCR and PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) analysis. The PCR product and the restricted fragment product were run on agarose gel electrophoresis. All the statistical analysis was done by using Statistical Package for the Social Sciences (SPSS) version no. 20.0. The demographic characteristic among the modifiable risk factors, this study found the significant difference observed in HbA1C (p<0.001), triglyceride (p<0.008) and total cholesterol (p<0.04). However, there was no significant difference found in age, gender, body mass index, diastolic and systolic blood pressure, blood glucose, high density lipoprotein and low density lipoprotein and aspartate aminotransferase, alanine aminotransferase in case subjects when compare to the controls. Among the non-modifiable risk factors (genetic risk factors) there was, significant difference was observed for genotypic and allelic distributions between T2DM patients and non-T2DM subjects for gender of SLC22A2 rs 145450955(p<0.031), for allelic distributions (p<0.009) in controls, and was significant in TC (p<0.047), AST (p<0.015) in diabetics and significant LDL (p<0.029) in controls based on phenotype. SLC22A3 rs2292334 genotypic distribution was significant (p<0.022) and for allelic distributions (p<0.001) in controls and was significant in FBS (p<0.037) in controls based on phenotype. SLC22A3 rs 3088442 genotypic distribution (p<0.016) in diabetics, and significant in LDL (p<0.013) based on phenotype. The association of SLC22A3 are considered as genetic risk factors for the development of T2DM in male based on genetic models and gender. However, similar studies with significantly larger samples are highly recommended to verify how candidate genes are associated with regard to T2DM in Indian and other ethnics. Performing genetic association on other polymorphisms of the candidate genes studied as well as other polymorphisms in other genes.